(untitled) (Research, Society and Development, 2022)
Objective. To analyze food promotion on the cover and inside pages of supermarkets circulars. Methods. Promotional circulars data were collected from five supermarket chains in Rio de Janeiro (Brazil) in August 2019. Food was categorized according to the NOVA classification: fresh food or minimally-processed food (FF/MPF), processed culinary ingredients, processed food, and ultra-processed food (UPF). The density of the food groups on the cover and inside pages of circulars was calculated, and the comparison was performed using paired T-test or paired Wilcoxon test, depending on the normality and homogeneity of the data distribution. Results. A total of 59 circulars were analyzed and 7665 foods were identified, of which 55.6% UPF and 27.7% FF/MPF. FF/MPF are more present on the cover while the UPF are more present on the inside pages of the circulars. Conclusion. The cover of circulars does not reflect the entire contents. On the cover, foods with better nutritional profile are more present than inside of the circulars. It is necessary to develop government programs that regulate the promotion of foods in supermarkets circulars.